2023
DOI: 10.1080/20008066.2023.2182820
|View full text |Cite
|
Sign up to set email alerts
|

Shame, depression, and complicated grief among suicide loss-survivors: the moderating role of self-disclosure

Abstract: Background: Suicide-loss survivors (SLSs) are recognised as an at-risk population for several psychiatric complications, including complicated grief (CG) and depression (SI). However, whereas shame is known as one of the characteristics of this population, knowledge about possible psychological processes which may moderate the contribution of shame levels to CG and depression in the aftermath of suicide loss is sparse. This study examines the role of self-disclosure – the inclination to share person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
1
5
0
4
Order By: Relevance
“…As to the second hypothesis, we firstly found that SLSs with higher levels of shame endured higher CG levels and depressive symptoms. These findings align with many reviews and theoretical papers indicating that suicide‐related shame and guilt in the aftermath of suicide loss carries a considerable deleterious psychological effect (Jordan, 2020; Levi‐Belz & Hamdan, 2023; Pitman et al, 2014). It is thus reasonable to suggest that when SLSs feel guilt or shame following the suicide event, it reinforces self‐stigmatization and loneliness (Hanschmidt et al, 2016), ultimately leading to difficulties adjusting to the post‐suicide life, as reflected in higher CG and depressive symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…As to the second hypothesis, we firstly found that SLSs with higher levels of shame endured higher CG levels and depressive symptoms. These findings align with many reviews and theoretical papers indicating that suicide‐related shame and guilt in the aftermath of suicide loss carries a considerable deleterious psychological effect (Jordan, 2020; Levi‐Belz & Hamdan, 2023; Pitman et al, 2014). It is thus reasonable to suggest that when SLSs feel guilt or shame following the suicide event, it reinforces self‐stigmatization and loneliness (Hanschmidt et al, 2016), ultimately leading to difficulties adjusting to the post‐suicide life, as reflected in higher CG and depressive symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…(8, Shame, sebagaimana dikutip oleh Levi-Belz dari Brown, adalah perasaan dan penghayatan yang sangat menyakitkan akibat adanya keyakinan bahwa diri kita tercela dan tidak berharga untuk diterima sebagai bagian dari suatu komunitas. (8) Levi-Belz juga mengutip beberapa hasil studi dari Jordan, Pitman, dan Tangney, yang mendapatkan bahwa shame menyebabkan distres yang lebih tinggi dan secara emosional lebih menyakitkan dari rasa bersalah (guilt). (22) Stigma yang dialami oleh penyintas kehilangan bunuh diri terjadi dalam dua perspektif.…”
Section: Shame Dan Stigmaunclassified
“…Yang pertama adalah self-stigma yang sangat berkaitan dengan shame, nilai moral tentang bunuh diri, rasa bersalah sebagai penyebab bunuh diri dan kegagalan dalam mencegah hal tersebut. (2,8,23) Perspektif yang kedua adalah stigma di masyarakat.…”
Section: Shame Dan Stigmaunclassified
See 1 more Smart Citation
“…Self-disclosure can help individuals rebuild positive social sharing beliefs ( Tajvar et al, 2018 ; Levi-Belz and Hamdan, 2023 ). Social support influences the self-disclosure of individuals ( Bu et al, 2023 ; Ricciardi et al, 2023 ); adequate social support helps individuals maintain a favorable emotional experience and increase self-confidence.…”
Section: Introductionmentioning
confidence: 99%